Arsenic Uptake in Durum Wheat (Triticum durum Desf.) as Influenced by Soil Tillage Practices and Fertilization Sources in Mediterranean Environment - Ilenia Bravo; Mariam Atait; Ilenia Colamatteo; Roberto Mancinelli; Mohamed Allam; Patrizia Papetti; Emanuele Radicetti (Agriculture)
Nowadays, arsenic (As) accumulation in agricultural soils and its transfer in crop yields is representing a growing concern that threatens food safety and security in the Mediterranean environment. Soil tillage and fertilization may increase the accumulation of As in plant tissues; therefore, there is a need to develop sustainable agronomical practices capable of supporting crop yield while mitigating As accumulation. The current study was carried out through a 7-year experiment with the aim of evaluating the As uptake by different parts of the durum wheat plant. The experimental treatments include the following: (i) three soil tillage practices (plowing, subsoiling, and spading) and (ii) two fertilization methods (mineral and organic). A factorial randomized complete block design with three replications was adopted. The experimental period refers to the 2018/2019, 2019/2020, and 2020/2021 growing seasons. The results suggest that the maximum level of As was found in plant roots and the minimum in wheat kernels. The chemical fertilization as 2020 × Mineral (1.522 mg As kg−1 d.m.) and 2020 × Plowing (1.855 mg As kg−1 d.m.) had the maximum As content in the roots. Conversely, the content of As was at a minimum in the wheat kernels for organic fertilization as 2021 × Organic (0.012 mg As kg−1 d.m.) and subsoiling tillage as 2021 × Subsoiling (0.008 mg As kg−1 d.m.). Moreover, the application of an organic fertilization source as a tool for enhancing the soil organic matter content also significantly decreased the As content. The results suggest that reduced tillage practices and the adoption of organic amendment could be classified as sustainable agronomic practices in agri-food systems, which are able to improve plant quality and assure a safe consumption of wheat kernels.